THE DYNAMICS OF BETAWI SCHOLARS AND THE SUCCESS OF DA'WAH IN THE SOCIAL AND CULTURAL CONTEXT OF THE 20TH CENTURY IN JAKARTA - Siti Fatimah Hasbiallah; Daud Rasyid; Marliza Oktapiani (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This study examines the dynamics of da'wah in Jakarta in the 20th century, focusing on the adaptation of da'wah methods and media in the face of social and cultural changes Jakarta, formerly known as Batavia, underwent significant transformations due to Dutch colonialism, rapid urbanization, and changes in social structure. This study uses a qualitative method with analysis of historical literature, da'wah documentation, and interviews with religious leaders to explore how Betawi scholars in the 20th century adapted their da'wah approach to Jakarta's social and cultural conditions. The results of the study show that da'wah by Betawi scholars in Jakarta during that period was carried out in taklim assemblies and educational institutions (madrasah, pesantren) by adopting various modern media, including lectures, writings, and audiovisual publications, to reach a wider audience. Betawi scholars have succeeded in carrying out their da'wah by combining religious values and local traditions in Betawi society. Da'wah activities and social and cultural contributions were found to be important things, namely leadership that is respected for its charisma, wisdom, and humility. Betawi scholars often mediate social conflicts, as well as a source of advice and guidance for the community. The da'wah of Betawi scholars is not only ritual, but also includes social and cultural aspects and plays a role in preserving Betawi Islamic traditions. This pesantren is an educational center that produces scholars and community leaders who contribute widely in various areas of DKI Jakarta. The conclusion of this study highlights the importance of flexibility in da'wah methods and their impact on the understanding of Islam among the people of Jakarta. The results are expected to enrich the literature on da'wah and help develop more effective da'wah methods in the future.